2020
DOI: 10.7150/jca.39562
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine TNF-α promotes invasion and metastasis of gastric cancer by down-regulating Pentraxin3

Abstract: As a novel multifaceted player in cancer, Pentraxin3(PTX3) was recognized to be a possible factor related with tumor development. Recent researches have indicated that PTX3 is involved in immune response, inflammation, as well as cancer, and is greatly controlled by numerous cytokines. Tumor necrosis factor (TNF-α) is an imperative cytokine that demonstrates an extensive array of biological consequences in gastric cancer advancement. Here, we inspected the expression of PTX3 in gastric carcinoma tissues along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…Furthermore, the CSC phenotype can be obtained by inducing the tumor EMT state 20 . In our previous studies, we have confirmed that overexpression of PTX3 can inhibit the EMT process in GCCs (BGC-823 and SGC-7901) 17 . However, we have not yet proved whether PTX3 affects the stemness of GCCs.…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…Furthermore, the CSC phenotype can be obtained by inducing the tumor EMT state 20 . In our previous studies, we have confirmed that overexpression of PTX3 can inhibit the EMT process in GCCs (BGC-823 and SGC-7901) 17 . However, we have not yet proved whether PTX3 affects the stemness of GCCs.…”
Section: Resultssupporting
confidence: 63%
“…Evidence from clinical and experimental studies has indicated that TAMs promote the invasion and metastasis of solid tumors by releasing a variety of cytokines. We have proven through previous studies that PTX3 can affect chemokine to inhibit the invasion and metastasis of GCCs 17 . Therefore, we speculated whether PTX3 is linked to macrophages.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Our findings revealed that cell proliferation was increased following LPS stimulation in AGS cells. Earlier researches demonstrated the effects of IL-1β (27), and other inflammatory cytokines (28) in gastric cancer progression and showed that upregulation of CBRs led to the activation of downstream pathways involved in cell progression and survival and cancer cell invasion through some pathways such as PI3K/PKB phosphorylation (29,30), ERK cascade (31), and CXCR4/CXCL12 (32). Taken together, previous results and findings suggest that inflammatory cytokines may exert their function through upregulation of CB1R.…”
Section: Discussionmentioning
confidence: 62%